HAK-HAK PEREMPUAN DALAM PENGARUSUTAMAAN RATIFIKASI CEDAW DAN MAQĀṢID ASY-SYARĪ‘AH - AGUSTINA, ARIFAH MILLATI (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
A concern in the elimination of discrimination against women with special treatment is recognized by the international community. This is manifested in the convention on the elimination of all forms of discrimination against women (CEDAW), which aims at achieving the equality and justice. The elimination of discrimination acts as the mainstreaming of women towards the gender equality. It is even formulated as a basic need for the promotion of the human rights in the millennium development goals. This article discusses maqāṣid asy-syarī'ah with the principle of substantive equality, the principle of non-discrimination in the fulfillment of basic freedoms and human rights, and the principle of state obligation that has the responsibility to ensure the realization of the right equality of men and women using the approach of al-maṣlaḥah.[Perhatian pada penghapusan diskriminasi terhadap perempuan dengan perlakuan khusus diakui oleh dunia Internasional. Hal ini diwujudkan dalam Convention on the Elimination of All Forms of Discrimination Againts Women (CEDAW) yang bertujuan untuk mencapai persamaan dan keadilan. Penghapusan diskriminasi tersebut berperan sebagai pengarusutamaan perempuan menuju kesetaraan gender. Bahkan hal ini dirumuskan sebagai kebutuhan dasar pemajuan hak asasi manusia dalam millenium development goals. Tulisan ini mendiskusikan maqāṣid asy-syarī'ah dengan prinsip kesetaraan substantif, prinsip non-diskriminasi dalam pemenuhan kebebasan-kebebasan dasar dan hak asasi manusia, serta prinsip kewajiban negara yang memiliki tanggungjawab untuk memastikan terwujudnya persamaan hak laki-laki dan perempuan, dengan menggunakan pendekatan al-maṣlaḥah.]